(untitled) (Orfeu, 2021)
This paper deals with the creative practices in the context of the Progressive Education Association. The sources investigated were the journal of the same name produced by the association, as well as other documents related to the group dating from the 1920s, 1930s and 1940s. I start from a reflection on the focused sources and then develop the theme in such a way as to show that the creative practices enjoyed outstanding importance, both in the activities of experimental schools and in the writings in the press, promoting debates and pedagogical innovation.